Learning American Sign Language in High School : Motivation, Strategies, and Achievement - Rosen, Russell Scott (Book collections on Project MUSE., 2015)
"Reflecting the exponential growth of college courses offering American Sign Language (ASL) as a foreign language, high schools have followed suit with significant increases in ASL classes during the past two decades. Despite this trend, high school ASL teachers and program administrators possess no concrete information on why students take ASL for foreign language credit, how they learn new signs and grammar, and how different learning techniques determines their achievement in ASL. This new book addresses these issues to better prepare high schools in their recruitment and education of new ASL students. Author Russell S. Rosen begins with the history of ASL as a foreign language in high schools, including debates about the foreign language status of ASL, the situation of deaf and hard of hearing students in classes, and governmental recognition of ASL as a language. Based on his study of five high school ASL programs, he defines the factors that motivate students, including community and culture, and analyzes strategies for promoting language processing and learning. Learning American Sign Language in High School provides strategies for teaching ASL as a second language to students with learning disabilities as well. Its thorough approach ensures the best opportunity for high school students to attain high levels of achievement in learning ASL"--